Pelit Sebagai Alasan Fasakh: Kajian Terhadap Putusan Pengadilan Agama Bangko No.70/Pdt.G/2021/Pa.Bko - Muyassarah Hamid; Gunawan Sayuti; Mida Alvia (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out the procedure for applying for a divorce at the Bangko Religious Court for Case No. 70/Pdt.G /2021/PA.Bko and to find out the legal basis for the Judges' Consideration in Determining Case No. 70/Pdt.G/2021/PA.Bko Regarding the husband. who is stingy and the husband accuses the wife of cheating at the Bangko Religious Court. The method used in this research is a method with a qualitative descriptive approach, because this research is considered capable of analyzing social reality in detail. The data collection technique is carried out by observation, interviews and documentation. This research concludes that when filing for divorce, the plaintiff should file a complaint in writing or verbally with the religious court/syari'ah court. Then the lawsuit is submitted to the religious court/syariah court with several provisions, including that whose jurisdiction includes the defendant's residence, if the defendant's residence is unknown, then the lawsuit is submitted to the religious court/syariah court whose jurisdiction includes the plaintiff's residence, if it concerns fixed objects, then a lawsuit can be filed with the religious court/syariah court. Several things were taken into consideration by the judge in the Bangko Religious Court Decision No. 70/Pdt.G/2021/Pa.Bko, among others, peace efforts have been made between the plaintiff and the defendant, domestic commotion that has been going on for a long time, the presence of evidence and witnesses in the trial, and surah ruum verse 21 is also taken into consideration by the judge in decided the case granting the defendant's request..